Impact of Adequate Disinfection Techniques for Ultrasound-Guided Injections in Musculoskeletal Rehabilitation: A Scoping Review - Angelo Alito; Alessandro de Sire; Marco Di Gesù; Enrico Buccheri; Daniele Borzelli; Rita Chiaramonte; Umile Giuseppe Longo; Antonio Ammendolia; Michele Vecchio; Daniele Bruschetta (Diagnostics)
Background: Interventional physiatry is a branch of medicine that uses minimally invasive ultrasound-guided techniques for diagnosis and treatment in the musculoskeletal system. The aim of this scoping review is to investigate the sterilisation techniques used and the rate of infection with ultrasound-guided injections. Methods: PubMed was searched up to 30 September 2024 using the following search terms (“Ultrasound, Interventional”[mesh]) AND “Injections, Intra-Articular”[mesh]; “Ultrasound-guided intra-articular injection”. The inclusion criteria were randomised clinical trials, written in English, involving US-guided mini-invaexercissive procedures. Results: The search identified a total of 256 potentially relevant publications. After screening for duplication, inclusion, and exclusion criteria, 105 articles were eligible for data extraction. In 51 studies, the method of skin disinfection was not specified, 18 RCT reported a ’sterile condition’, 9 studies used povidone–iodine solution, 5 used alcohol, and 2 used chlorhexidine 0.5%. In 64 trials, the method of probe preparation was not specified, 11 trials described the use of sterile gel, 10 trials reported the use of a probe cover, sterile pad, or barrier, and 2 trials reported the use of chlorhexidine 0.5%; 41 studies reported mild adverse events and 4 serious adverse events. Conclusions: Taken together, the findings of this scoping review did not show a clear relationship between current sterilisation protocols and the prevention of the microbial contamination of the probes or the patient’s skin. The variation in protocols highlights the need for standardised guidelines and more rigorous studies to accurately determine the most effective disinfection practices.